2022
DOI: 10.3389/fonc.2021.795528
|View full text |Cite
|
Sign up to set email alerts
|

Participation and Yield of a Lung Cancer Screening Program in Hebei, China

Abstract: ObjectiveLung cancer screening has been widely conducted in Western countries. However, population-based lung cancer screening programs in Hebei in China are sparse. Our study aimed to assess the participation rate and detection rate of positive nodules and lung cancer in Hebei province.MethodIn total, 228 891 eligible participants aged 40–74 years were enrolled in the Cancer Screening Program in Hebei from 2013 to 2019. A total of 54 846 participants were evaluated as the lung cancer high-risk population by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
2
5
1
Order By: Relevance
“…The LDCT screening participation rate for nonsmokers was higher than that for smokers, as reported in other studies [ 13 , 14 ]. Studies have consistently shown that smokers have lower recognition of tobacco harm, lower health awareness, or preferred not to be notified of their status of lung cancer [ 14 - 18 ]. Women accounted for the majority of nonsmokers, and women had better awareness of cancer prevention than men [ 19 ].…”
Section: Discussionsupporting
confidence: 52%
“…The LDCT screening participation rate for nonsmokers was higher than that for smokers, as reported in other studies [ 13 , 14 ]. Studies have consistently shown that smokers have lower recognition of tobacco harm, lower health awareness, or preferred not to be notified of their status of lung cancer [ 14 - 18 ]. Women accounted for the majority of nonsmokers, and women had better awareness of cancer prevention than men [ 19 ].…”
Section: Discussionsupporting
confidence: 52%
“… 46 , 47 In a Chinese LCS program that achieved a participation rate > 50%, people who had never smoked had higher education levels, a family history of lung cancer, and occupational exposure, and had higher rates of participation. 48 Male participants have also been over-represented in international trials, 49 and more evidence is needed about the optimal strategies to recruit female participants. A lack of centralized patient registration systems in most WPR countries precludes the systematic mailing of invitations, appointment reminders, and recalls after screening.…”
Section: Resultsmentioning
confidence: 99%
“…Australia and Japan have the greatest number of CT machines per capita. 48 However, many WPR countries have few CT machines and limited numbers of appropriately skilled thoracic radiologists and radiographers (Table 2 ). Thoracic surgeons, clinical oncologists, and specialist oncology nurses are essential to the delivery of a LCS program.…”
Section: Resultsmentioning
confidence: 99%
“…16,17 Effective, high-quality programmes also require adherence to recommendations for follow-up investigations including recommended screening intervals. Summarized results of studies evaluating participation and adherence to follow-up are presented in Table 1, including data from screening populations in China 18 and the United States 19 as well as recommendations based on a British review of participation in clinical trials and pilot programmes. 20…”
Section: Screening Participation and Adherencementioning
confidence: 99%